METHODS FOR ASSESSING A CHILD'S READINESS FOR SCHOOL: A COMPREHENSIVE APPROACH (Conferencea, 2024)
This article discusses effective methods for evaluating a child's readiness for school, focusing on cognitive, emotional, and social dimensions. It highlights modern assessment tools and strategies that educators and parents can use to ensure a smooth transition to formal education. The study emphasizes the importance of identifying individual needs and providing targeted support to foster optimal development in preschool-aged children.